2017
DOI: 10.3390/rs9070716
|View full text |Cite
|
Sign up to set email alerts
|

Stem Measurements and Taper Modeling Using Photogrammetric Point Clouds

Abstract: Abstract:The estimation of tree biomass and the products that can be obtained from a tree stem have focused forest research for more than two centuries. Traditionally, measurements of the entire tree bole were expensive or inaccurate, even when sophisticated remote sensing techniques were used. We propose a fast and accurate procedure for measuring diameters along the merchantable portion of the stem at any given height. The procedure uses unreferenced photos captured with a consumer grade camera. A photogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…The main advantage of terrestrial CRP is that it produces similar outputs with lower hardware costs when compared to TLS systems. Only a few recent studies have explored this new approach [24][25][26][27][28]; they reported a root mean square error of DBH estimation from CRP that varied from 0.91 cm to 6.79 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of terrestrial CRP is that it produces similar outputs with lower hardware costs when compared to TLS systems. Only a few recent studies have explored this new approach [24][25][26][27][28]; they reported a root mean square error of DBH estimation from CRP that varied from 0.91 cm to 6.79 cm.…”
Section: Introductionmentioning
confidence: 99%
“…We created the point cloud using structure-from-motion [18][19][20][21], as implemented in Agisoft version 1.3.4 [22]. The Agisoft parameters used to process the images were based on the recommendations of Fang and Strimbu [15,23].…”
Section: Tree Segmentation From the Above Canopy Acquired Point Cloudsmentioning
confidence: 99%
“…A similar procedure, and consequently point cloud, was obtained from the images captured with GoPro camera. We produced separate point clouds for each device by processing the images with Agisoft version 1.3.4 [22] using the parameters of Fang and Strimbu [15,23]. The major difference between the two-point clouds (i.e., from Nikon and from GoPro) being their positioning, one in relative coordinates (i.e., disconnected from reality-Nikon), and the other relatively positioned in the correct region (i.e., no accuracy-GoPro).…”
Section: Generation Of Point Clouds From Below Canopy Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have used terrestrial SfM photogrammetry to reconstruct trees within plots [20][21][22][23][24][25] while others focused on individual trees [12,19,[26][27][28][29]. The root mean square error (RMSE) of the DBH estimation is generally more accurate for studies focused on individual trees, where the RMSE is mainly < 1 cm; whereas, for those in which whole plots are reconstructed, the RMSE is a couple of centimetres.…”
Section: Introductionmentioning
confidence: 99%